2023
DOI: 10.24843/jh.2023.v27.i01.p02
|View full text |Cite
|
Sign up to set email alerts
|

The The Lexical Equivalence in the Translation of the English Noun ‘Love’ into Indonesian

Abstract: This study aims at finding out the translation variations as the lexical equivalences of the English noun ‘love’ into Indonesian, and analyzing the translation shifts. The data were taken from the parallel corpus containing the English expressions with the noun ‘love’ and their translations. The data were collected through the documentation method and analyzed qualitatively. The results show that the translations of the English noun ‘love’ are varied with 21 lexicons. The translations are categorized into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Jakobson (1959) and Brata (2010) have shown that the role of context is significant in defining meanings. Context helps determine specific and clear meanings to the certain lexicon (Widiastuti & Indriani, 2023). The cultural and social setting can also be found in motivation, such as from the motivator personal experience background.…”
Section: Introductionmentioning
confidence: 99%
“…Jakobson (1959) and Brata (2010) have shown that the role of context is significant in defining meanings. Context helps determine specific and clear meanings to the certain lexicon (Widiastuti & Indriani, 2023). The cultural and social setting can also be found in motivation, such as from the motivator personal experience background.…”
Section: Introductionmentioning
confidence: 99%